ANTHROPOMETRIC EFFECTS DERIVING OF THE VARIATION'S INTENSITY IN CIRCUIT TRAINNING DURING MENSTRUAL CYCLE (Fiep Bulletin - online, 2011)
he menstrual cycle is characterized by rhythmic changes in production and secretion of peptide adeno gonadotropic of pituitary which determine the beginning of the new growth in ovaries follicles. One of the follicles finally becomes mature and ovula in around 14 day. During the growth of follicles occurs mainly secretion of estrogen. After reproduction, follicle-secreting cells become in secret luteum, that large quantities of female hormones progesterone and estrogen. After 2 weeks, the luteum degenerates and, consequently, the hormones estrogen and progesterone ovarian decrease sharply-mind and begins to menstruation. Next, then, a new ovarian cycle; these hormones also influence the availability of different substrates for physical exercise, possibly also changes the circuit training performance. Workload variation has been discussed recently training as a way to mitigate hormonal changes arising from the menstrual cycle and consequently increase the effects of training. The present study was to examine the difference in the percentage of fat comparing eight weeks of training with constant load and eight weeks of training with such intensity variation. The percentage of fat was analyzed by skin creases method and determined by the Protocol of Pollock using a clinical Cescorf skinfold. Significant difference was verified in the variables analyzed. We found that for this case variations of intensity can bring more satisfactory results, but not conclusive taking into account the number of assessed which was small it shows the importance of research to better attesting this hypothesis.
Keywords: Ciclo menstrual; treino em circuito; variação de intensidade